A Novel Restraint Device for Injection of Galleria mellonella Larvae that Minimizes the Risk of Accidental Operator Needle Stick Injury - Dalton, James P.; Uy, Benedict; Swift, Simon; Wiles, Siouxsie (Frontiers in Cellular and Infection Microbiology, 2017)
Larvae of the insect Galleria mellonella are increasingly being used for studying pathogenic microbes and their virulence mechanisms, and as a rapid model for screening novel antimicrobial agents. The larvae (waxworms) are most frequently infected by injection of pathogenic organisms into the haemocoel through the insect’s prolegs. The mostly widely used method for restraining the waxworms for injection is by grasping them between the operator’s fingers, which puts the operator at risk of needle stick injury, an important consideration when working with highly pathogenic and/or drug-resistant microorganisms. While use of a stab proof glove can reduce this risk of injury, it does so at the loss of manual dexterity and speed, resulting in a more labour-intensive and cumbersome assay. We describe a simple cost effective device (the so-called ‘Galleria Grabber’) for restraining waxworms for injection that keeps the operator’s fingers clear of the needle thus reducing the risk of injury.